2010
DOI: 10.1177/0886260510363421
|View full text |Cite
|
Sign up to set email alerts
|

“You Owe Me”: Effects of Date Cost, Who Pays, Participant Gender, and Rape Myth Beliefs on Perceptions of Rape

Abstract: Sexual social exchange theory was applied to perceptions of a date rape by manipulating the cost of the date and who paid in vignettes presented to 188 U.S. college students, who then rated the characters' sexual expectations, blame, responsibility, and rape justifiability. Findings from this between-participant design partially supported predictions: When the man paid for an expensive date, men agreed more than did women that both characters should have expected sexual intercourse. Conversely, when the costs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
85
3
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 18 publications
1
85
3
5
Order By: Relevance
“…High scoring observers are also more likely to believe that the rape could have been avoided (Kopper, 1996). A recent study using regression analysis has even concluded that rape myth acceptance was the strongest predictor for participants' rape perceptions with β = .36 (Basow & Minieri, 2011). It is, therefore, suggested that rape myth acceptance should be one of the main targets in preventive programs developed for preventing sexual violence and for improving attitudes towards rape victims (Bohner et al, 2009).…”
Section: Rape Myth Acceptancementioning
confidence: 99%
See 1 more Smart Citation
“…High scoring observers are also more likely to believe that the rape could have been avoided (Kopper, 1996). A recent study using regression analysis has even concluded that rape myth acceptance was the strongest predictor for participants' rape perceptions with β = .36 (Basow & Minieri, 2011). It is, therefore, suggested that rape myth acceptance should be one of the main targets in preventive programs developed for preventing sexual violence and for improving attitudes towards rape victims (Bohner et al, 2009).…”
Section: Rape Myth Acceptancementioning
confidence: 99%
“…A limitation associated with these studies relates to the lack of control groups; although some studies investigate rape blame attributions amongst various professional groups, they often lack a control group from the general population, which makes it difficult to generalize and compare the findings. With regard to the variables of gender role attitudes and rape myth acceptance, many studies have found that these are important predictors for rape victim blaming and rape minimization (e.g., Basow & Minieri, 2011;White & Kurpius, 2002). However, other studies have concluded that they merely act as mediating variables between observer gender and rape victim blaming, with men generally portraying higher gender role attitudes and rape myth acceptance, which in turn leads to a higher degree of victim blame (Anderson & Lyons, 2005;Hammond et al, 2011).…”
Section: Conclusion and Summarymentioning
confidence: 99%
“…Higher rape myth endorsement was also shown to predict increased female victim blaming (e.g., Basow & Minieri, 2011;Bendixen et al, 2014;Cohn et al, 2009;Earnshaw, Pitpitan, & Chaudoir, 2011;Frese et al, 2004;Gerger et al, 2007;Grubb & Tarn, 2012;Hammond et al, 2011;Mason, Riger, & Foley, 2004;Newcombe et al, 2008;Paul et al, 2014). Men are thought to accept rape myths so as to justify sexual violence, whilst women endorse them to reject personal vulnerability to rape (Johnson, Kuck, & Schander, 1997).…”
Section: Rape Myth Acceptancementioning
confidence: 99%
“…Similar findings were reported by American research with undergraduate students. For instance, a study exploring the influence of the cost of a date rape, gender, and rape myth acceptance on female victim blaming (Basow & Minieri, 2011) indicated that higher victim blame was assigned in an expensive date scenario; overall, rape myth acceptance was the best predictor of female victim blaming (rather than participant gender). Furthermore, Hammond and colleagues (2011) examined the influence of rape myth acceptance, belief in a just world, and sexual attitudes on attributions of responsibility in an ambiguous date rape scenario.…”
Section: Rape Myth Acceptancementioning
confidence: 99%
“…Higher levels of rape myth acceptance have been linked to increased likelihood of sexual aggression (Basow & Minieri, 2011). Higher levels of rape myth acceptance also have the potential to lead to the underreporting of sexual assaults (Heath, Lynch, Fritch, & Wong, 2013).…”
Section: Rape Myth Acceptancementioning
confidence: 99%